The battle against dental caries: defeating biofilm formed by bacterial isolates using vanillin and plant essential oils: in vitro and ex vivo approaches - Manar M. Ahmed; Nehal E. Yousef; Momen Askoura; Galal Yahya; Amira M. El-Ganiny (Future Journal of Pharmaceutical Sciences)
Abstract Background Infections caused by biofilm-forming bacteria have significantly linked to dental plaque and caries. The aim of this study is to assess efficacy of some natural compounds in inhibition and eradication of biofilm formed by bacterial isolates from dental infections. Results Bacterial isolates were recovered from dental plaque/caries and identified using standard microbiological tests and 16S rDNA sequencing. The isolated bacterial strains include Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis, Klebsiella pneumoniae, and Escherichia coli. The antibiotic susceptibility was determined by disk diffusion method and revealed that the majority of isolates showed high antibiotic resistance, and 61% of isolates were found to be multidrug resistant. The biofilm formation capacity of isolates was investigated using microtiter plate assay. Among the 77 bacterial isolates, seventeen showed moderate biofilm formation capacity, twenty-two showed near-moderate, thirty-four had weak biofilm-forming capacity, and four were non-biofilm producers. The antibiofilm activity of tested compounds (rose and jasmine oils, propolis, vanillin, and vinegar) was evaluated against isolates with highest biofilm-forming capacity. The in vitro antibiofilm ability of tested substances were investigated alone or in combination with each other to evaluate their ability to prevent biofilm formation or destroy preformed single-/multispecies biofilms. Finally, antibiofilm ability of tested combination was evaluated ex vivo on natural teeth. Our results showed that vanillin in combination with rose or jasmine oils showed promising biofilm inhibition and biofilm eradication activities in both the in vitro and ex vivo models. Conclusions Dental plaque and caries can be successfully prevented using combination of vanillin with rose or jasmine oils, and these compounds can be incorporated in new anticaries dental formulations.